(untitled) (Research, Society and Development, 2022)
Introduction: The pandemic of COVID-19 shook the foundations of modern societies, bringing numerous significant biopsychosocial consequences, which should be highlighted and analyzed in order to structure viable ways to overcome them. Objective: The present study aimed to evaluate the biopsychosocial impacts caused by the pandemic of COVID-19. Materials and Methods: This is an integrative literature review about the biopsychosocial consequences caused by the COVID-19 pandemic. The PICO strategy was used to develop the guiding question. Moreover, the descriptors "COVID-19"; "Psychosocial Impact"; "Health" were cross-referenced with the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar, and Virtual Health Library (VHL) databases. Results and Discussion: A significant portion of the articles indicated a correlation between the pandemic of COVID-19 and impacts on the biopsychosocial sphere, such as the manifestation of negative feelings and psychic suffering. In addition, other articles approached the importance of the practice of physical exercises to face the coronavirus, and another part of the articles indicated the direct involvement of health care workers. Conclusion: It was possible to realize that the pandemic scenario compromised the most diverse areas of the biopsychosocial context, reinforcing the need to give new meaning to the health-disease process, based on a more humanistic and social approach.